STUDY LAW FIRM CAPITAL ROLE IN IMPROVING ECONOMY STATE VENTURA INDONESIA - aryani witasari; Indah Setyowati (UNISSULA, 2019)
Venture capital is one of the financial institutions whose existence is still relatively new. Institutional and formal venture capital is a new venture there after the release of Presidential Decree No. 61 of 1988 on Financing Institutions and MoF No. 1251 / KMK.013 / 1988 on Conditions and Procedures for Financing Institutions. Both this regulation represents a milestone development of the venture capital law.This research uses descriptive analytical approach, using normative juridical approach or approaches normative-legal method research approach, or by Zainudin called normative legal research or doctrinal legal research, namely legal research using secondary data.The role of venture capital firms is very strategic, Venture capital has a great potential to contribute to business development. Small companies which have good prospects but do not have enough capital and do not have access to banks can thrive with the support of capital from venture capital. With venture capital, the new company would like to start a business activity could also be easily run business originally.In the mechanism of venture capital, there are at least three elements that are directly involved, namely: capital owners who want a high profit from its equity. Capital from various sources or investors are collected in a container or a special institution established for that purpose; or so-called venture capital funds.